2014
DOI: 10.1128/aem.03061-13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Virulence Genes Associated with Pathogenic Escherichia coli Strains Isolated from Domestically Harvested Rainwater during Low- and High-Rainfall Periods

Abstract: bThe possible health risks associated with the consumption of harvested rainwater remains one of the major obstacles hampering its large-scale implementation in water limited countries such as South Africa. Rainwater tank samples collected on eight occasions during the low-and high-rainfall periods (March to August 2012) in Kleinmond, South Africa, were monitored for the presence of virulence genes associated with Escherichia coli. The identity of presumptive E. coli isolates in rainwater samples collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…Apart from these, other studies assessing the quality of harvested rainwater are available for different parts of the world: Lye (1987) in Kentucky-USA, Fujioka et al (1991) in Hawaii, Coombes et al (2000) in NSW-Australia, Handia (2005) in Zambia, Hernandes and Vieira (2005) in Southeast Brazil, Peters et al (2008) in Bermuda, Ahmed et al (2009) in SEQAustralia, Daoud et al (2011) in Palestine, Gikas and Tsihrintzis (2012) in Northeast Greece, Shuster et al (2013) in Ohio-USA, Van der Sterren et al (2013) in Sydney, and Dobrowsky et al (2014aDobrowsky et al ( , 2014b in WC-South Africa. Finally, a summary of the reports on the chemical and biological quality of harvested rainwater tanks can be found in Kwaadsteniet et al (2013).…”
Section: Quality Threat 2: Lack Of Maintenance Periodic Cleaning Andmentioning
confidence: 98%
“…Apart from these, other studies assessing the quality of harvested rainwater are available for different parts of the world: Lye (1987) in Kentucky-USA, Fujioka et al (1991) in Hawaii, Coombes et al (2000) in NSW-Australia, Handia (2005) in Zambia, Hernandes and Vieira (2005) in Southeast Brazil, Peters et al (2008) in Bermuda, Ahmed et al (2009) in SEQAustralia, Daoud et al (2011) in Palestine, Gikas and Tsihrintzis (2012) in Northeast Greece, Shuster et al (2013) in Ohio-USA, Van der Sterren et al (2013) in Sydney, and Dobrowsky et al (2014aDobrowsky et al ( , 2014b in WC-South Africa. Finally, a summary of the reports on the chemical and biological quality of harvested rainwater tanks can be found in Kwaadsteniet et al (2013).…”
Section: Quality Threat 2: Lack Of Maintenance Periodic Cleaning Andmentioning
confidence: 98%
“…Genes from the ETEC, EPEC and STEC pathotypes were detected consistently, but genes from the EIEC and EAEC pathotypes were only found occasionally, and never in the rainy season or in winter (Akter et al, 2013). EAEC was found in 16% of 80 samples from domestic rainwater harvest tanks during a longitudinal study in a high-population-density, urban setting and in river water samples in South Africa (Obi et al, 2004;Dobrowsky et al, 2014). In a study of pre-treated water in a drinking water treatment plant in Taiwan, EAEC-associated genes were found in 3.6% of 55 water samples, alongside with high levels of other potentially pathogenic E. coli (Huang et al, 2011).…”
Section: Outbreaks Of Gastrointestinal Disease Associated With Multipmentioning
confidence: 99%
“…Moreover, in fluoride prone areas such as AERV, rainwater is expected to have lower concentrations of toxic geogenic contaminants such as F, U, As, and heavy metals than groundwater. However, a number of studies have shown that rainwater may contain potentially toxic physicochemical and microbial contaminants [69][70][71][72][73][74].…”
Section: Physico-chemical and Microbial Quality Of Rainwatermentioning
confidence: 99%
“…The bulk of contaminants reported in rainwater are often acquired from atmospheric deposition, roof materials, and conveyance and storage facilities [69][70][71][72][73][74]. A study by Gwenzi et al [75] presents a detailed discussion of the occurrence of various contaminants in roof rainwater, and the key factors influencing its quality, including nature and age of roof materials, weather conditions and land use practices.…”
Section: Physico-chemical and Microbial Quality Of Rainwatermentioning
confidence: 99%